Asking questions in biology : - Barnard, C. J. (Longman Scientific & Technical, 1993)
This text provides an enjoyable introduction to quantitative biology for students in the biological sciences and explains important techniques and analytical methods in the context of the student's aim: to answer biological questions as clearly as possible. The authors introduce the various stages in the process of enquiry, starting with unstructured observation and working through to the production of a complete written report. Logical steps guide the student through each stage of the enquiry to the point where he or she will be able to carry out an open-ended project as well as cope with more structured practical work.